التراث العمراني بمدینتي فاس ومكناس القديمتين : المقومات والتنمية المحلية - فاطمة الزهراء بوجدي (جامعة سيدي محمد بن عبد الله ، كلية الآداب و العلوم الإنسانية - ظهر المهراز-، فاس, 2020)
Urban heritage is of great importance to the international and local communities; firstly, because of the various human and national values it embodies Secondly, because it is considered a source of the national income. Thirdly, it is essential for the economic and the local development, as well as for the protection of the cultural identity. Morocco is loaded with a rich and varied urban heritage due to its historical depth and cultural convergence. It has classified many of its cities as World Heritage Sites and a legacy to all mankind. In this context, the ancient cities are the main pillar of the national heritage, as many of them have been recognized as historical sites and landmarks within the World Heritage List. The cities of Fez and Meknes are among the most important Moroccan cities at the national level. They are famous for their history and ancient heritage, especially after they were classified as a world heritage by the UNESCO. The deteriorating situation that the two cities endure together, especially after the succession of collapses, whether at the level of some historical monuments or at the level of buildings, the thing that precipitated the establishment of a set of programs and projects in order to prevent and rehabilitate them as well as to protect human lives from this collapse. The damage of the old fabric in these two cities, is not only the result of one or two factors, rather, it is the outcome of a group of interconnected and interrelated factors, in the context of effect and affected relationship, which contributed greatly to the extinction and collapse of a group of historical monuments. Faced with the severity of the deterioration experienced by the two cities during recent decades, a set of practical steps and procedures were adopted to address this problem, which is reflected in the rehabilitation of historical monuments and the treatment program for fallen housing, through the restoration of some old architectural appearance, and improving the living conditions of the target population and enabling it to benefit from necessary services. These programs, which are included within the framework of the reconsideration approach of the two cities, would contribute to improving the urban scene, achieving socioeconomic development of the local population, and preserving the ancient genuine character of these two-ancient civilizations.
Keywords: Interface, Ressources, Sociétés et Dynamiques Territoriales; جغرافيا; التراث العمراني; مدینتي فاس ومكناس القديمتين; المقومات والتنمية المحلية